A theory of government procrastination - Taiji Furusawa; Edwin L.-C. Lai (Center for Economic Studies and ifo Institute (CESifo), 2011)
We present a theory to explain government procrastination as a consequence of its present-bias resulting from the political uncertainty in a two-party political system. We show that under a two-party political system the party in office tends to be present-biased. This may lead to inefficient procrastination of socially beneficial policies that carry upfront costs but yield long-term benefits. However, procrastination is often not indefinite even as we consider an infinite-horizon game. There exist equilibria in which the policy is implemented, and in many cases carried out to completion in finite time. When the net social benefit is large, there is no procrastination problem. When the net social benefit is small, the policy can be procrastinated indefinitely, though there may co-exist some gradual implementation equilibria. When the net social benefit is intermediate in magnitude, there are all sorts of procrastination equilibria, including gradual implementation. The theory predicts that a government with a more strongly predominant party tends to procrastinate less.
Keywords: C70; D78; D60; 330; present-bias; procrastination; policy implementation; Politik; Regierung; Zeitpräferenz; Kosten-Nutzen-Analyse; Demokratie; Wahlkampf; Theorie